Perancangan Alat Pendeteksi Kebocoran gas dan Pendeteksi api Berbasis Internet Of things Menggunakan Arduino uno - Thamrin Thamrin; Sri Dia Purnamasari (Universitas Negeri Padang, 2021)
The purpose of making this tool is to make a gas leak detector and internet of things-based fire detector using Arduino. The manufacture of this tool uses several components such as the MQ2 sensor, sensor flame, Arduino Uno, ESP8266 MCU node, Buzzer, Exhaust fan, and also a smartphone. so that the role of LPG (Liquefied Petroleum Gas) at this time is very important for human life. In this tool, there are two sensors, namely the MQ2 sensor and the sensor flame as well as the fan and buzzer as indicators. As for the microcontroller using Arduino Uno and NodeMCU ESP8266. The working principle of this tool is monitoring via a cellphone that is always active to find out the situation, around when the mq2 sensor detects the presence of gas, the fan will rotate as a first step so that the gas does not spread throughout the room and when the sensor flame detects a fire, the buzzer will sound.